Jundiá Fish Skin (Rhamdia quelen): An Unexplored By-product with Great Potential to Be Used as a Novel Source of Collagen. Issue 8 (14th September 2021) - Da Silva, Camila Giacomelli; Rodrigues, Angela Souza; Toniasso, Daniela Pedrolo Weber; Morisso, Fernando Dal Pont; Bastianello Campagnol, Paulo Cezar; Mello, Renius de Oliveira; Dornelles, Rosa Cristina Prestes; Kubota, Ernesto Hashime
ABSTRACT: For the first time, the skin of jundiá fish ( Rhamdia quelen ) (JS) was used to isolate acid-soluble collagen (ASC) and pepsin-soluble collagen (PSC). The ASC and PSC showed levels of 89.7 and 90.1% of protein, respectively. Fourier transform infrared spectroscopy (FTIR) indicated that the samples had groups in the amide region (A, B, I, II, and III) and that the helical conformation was not affected by the extraction methods. Furthermore, Sodium dodecyl-sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) showed that the extracted collagens were Type I and that they presented high denaturation temperatures (57.7 and 59.9°C for ASC and PSC, respectively). ASC and PSC exhibited positive results in terms of technological properties. Thus, JS represents a novel source of collagen that can be used on an industrial scale.